Adapting Historical Knowledge Production to the Classroom
XII, 258 p.
Keywords: The aims of this book are: • to contribute to professional development of those directly involved in science education (science teachers, elementary and secondary science teacher advisors, researchers in science education, etc), • to contribute to the improvement of the quality of science education at all levels of education with the exploitation of elements from History of Science incorporated in science teaching –it is argued that through such approaches the students’ motivation can be raised, their romantic understanding can be developed and consequently their conceptual understanding of science concepts can be improved since these approaches make science more attractive to them– and • to contribute to the debate about science education at the international level in order to find new ways for further inquiry on the issues that the book is dealing with. The book is divided in two parts: The first expounds its philosophical and epistemological framework and the second combines theory and praxis, the theoretical insights with their practical applications.